The Performance of Lecturer in the Development of Academic Culture in Ilmu Tarbiyah Al-Hilal College of Sigli - Sulaiman Sulaiman; Fuad Fuad; Muhammad Iqbal; Muhammad Muhammad (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
Ilmu Tarbiyah Al-Hilal College of Sigli is an institution of higher education and a center for strategic study of Islamic religious knowledge that requiring lecturers who have the ability and reliable performance. This study is aimed to determine the performance of lecturer at the Tarbiyah Al-Hilal Sigli College of Sciences. This study uses a descriptive approach and qualitative methods with data collection techniques used were documentation, observation and interviews. Research subjects were College chairpersons, study program chairpersons, lecturers, administrative chairpersons, and students. Data analysis were performed by: data reduction, data presentation, and drawing conclusions. This research shows that: 1) the performance of lecturers in conducting the learning process has followed the principles of learning, this is seen from the planning, implementation and evaluation of learning carried out by lecturers. 2) The motivation of lecturers in conducting the learning process is reflected in the willingness and awareness of lecturers in carrying out the tasks assigned to them.